ESTIMTES OF MORTALITY OF NEMATOPALAEMON TENUIPES (HENDERSON) JN THE BOMBAY WATERS - Sukumaran, K K (Indian Journal of Fisheries, 2011)
The fishery of Neinatopuhienwn tcnuipes showed wide flluotuations. However,no downward trend in the catch or c.p.u.e. is indicated. The estimated annual totalmortality rate in males and females is found to be 3.68 and 2.98 at Versova whileit is 3.64 and 3.11 at Sassoon Docks.